Memorandum on the Beveridge Report - Beveridge, William Henry Beveridge, Baron, 1879-1963 (London : Communist Party of Great Britain)
1943-02 1943 1940s 28 pages Here is the expenditure on "other items" of an average urban working-class household in 1938. s. d. Soda, soap and other cleaning and polishing materials 1 1½ Household equipment (Pottery and glass, hollow-ware, drapery, brushes, Boor coverings, furniture, etc.) 2 11½ Travelling 2 3 Laundry charges 0 6½ Hairdressing, shaving 0 6¼ Doctor, dentist, optician, nursing, medicine, drugs, hospital payments 2 0¾ Trade Union subscriptions 1 4¼ Newspapers and other periodicals 1 0 Entertainments 1 4½ National health, pensions, and unemployment assurance........................ 2 0¾ Other insurance and pension funds 2 4½ Tobacco and cigarettes 2 6½ Other expenditure 5 9¾ Now a great deal of this expenditure is inescapable when unemployed or sick. Provision for these other items is made in the Beveridge Report under the head of fuel, light and household sundries, and 4/- is allotted in terms of 1938 prices. Of this sum we are told that 3/7 per week was spent by the poorer working-class households for fuel and light in 1938. This would leave only 5d. for "other items" in terms of 1938 expenditure, or 6¼d. in terms of assumed post-war prices. Even if we allowed a cut in expenditure on light and fuel, it is doubtful if more than 1/- per week could be provided for "other items" on the basis of the Beveridge scales. The expenditure on "other items" by an urban working-class family in 1938 was 25/3 for a family of 3¾ adults, or, roughly, 13/6 for two adults. 11 15X/2/103/272